Implementasi Instrumen Penilaian Sikap di SDN Gunungsaren Bantul - Itsna Rifiana Ulfa (PALAPA, 2019)
The background of the problem held by this research is to find out the implementation of attitude assessment applied in schools. The attitude or affective aspect is an important part of the learning process, but many schools only focus on cognitive aspects. A good attitude must be instilled in every student and there is on need to think about it because it is absorbed in his daily behvior. This study aims to determine whether attitude assessment has been applied to the maximum in learning and the apllication of attitude assessment techniques in learning. The research method is a qualitative field research with a descriptive approach. Obtained from observations, interviews and documentation. Interviews were conducted with PAI’s teachers to find out whether the attitude assessment had been applied ti the maximum or not, observations were modw to find out the activities of teachers in assessing student’s attitudes in learning, and documentation was used to take an attitude assessment and photo form that could strengthen the evidence of the findings from interviews and observations. The results of this study indicate that the assessment of attitude has been apllied in learning, it is proven that students always try to be better with the prefix that only wants to get value but this change is implemented continuously so that it becomes a habit in everyday life.